Analisis Kebutuhan Dan Perancangan Sistem Informasi Operasional Apotek Menggunakan Pendekatan Manajemen Operasional, Persediaan, Dan Pelayanan (Studi Kasus: Apotek Griya Winaya) - Rosliani, Elin (Universitas Multi Data Palembang, 2025)
Pharmacies are healthcare service units that require fast, accurate, and standardized operational processes. Information systems play a crucial role in supporting stock management, prescription services, product returns, and financial reporting. This study aims to analyze the business processes of Apotek Griya Winaya in order to formulate the requirements for a web-based information system that can improve operational efficiency. The research employed field observation, interviews, and documentation, based on a student observation report from the Information Systems Study Program at Institut Pendidikan Indonesia Garut. The findings reveal that most operational activities are still performed manually, including stock recording, product returns, daily transactions, and financial reporting. These conditions increase the risk of errors, data inaccuracy, and potential expired stock. Based on the analysis, the study proposes information system requirements consisting of FEFO-based inventory management, digital prescription services, automated product return management, digital reporting, and managerial dashboards. This research contributes to the development of an efficient and accurate pharmacy information system that meets the needs of modern pharmaceutical operations.